Ethiopia's secondary school leaving examinations system: A glimpse inside its governance, management, and potential consequences - Tadesse , Tefera; Wale , Zelalem Teshome (Bahir Dar Journal of Education, 2025)
Nationally administered secondary school leaving examinations, or high school exit examinations, are instrumental in shaping students' futures, serving as a gateway to higher education, career opportunities, and personal growth. As pivotal milestones, these exams significantly influence students' opportunities and outcomes, making them a central focus of policy discussion. As a result, these examinations have been the focus of much policy debate. These examinations must be effectively administered and managed to ensure fairness, accuracy, and reliability in assessing students' knowledge and competencies. During the 2021–22 and 2022–23 academic years, Ethiopia's Ministry of Education and the National Educational Assessment and Examination Agency (NEAEA) relocated the administration of secondary school-leaving examinations from individual schools to public universities. Changing an examination system often requires different leadership and management skills, structures, and approaches than those needed for maintaining the familiar systems. The Ministry disclosed the students' terrible exam results but did not mention their management, governance, or the consequences of this assessment reform process. Despite the Ministry's claim that the 2022–23 academic year taught it some lessons, the outcomes did not indicate any improvement. This paper highlights key features of Ethiopia's secondary school leaving examinations and presents a framework for critically evaluating their management, governance, and potential outcomes of the reform process. By doing this, we might contribute to developing an impartial, trustworthy, and effective evaluation system.